Dynamics of viral disease outbreaks: A hundred years (1918/ 19–2019/20) in retrospect ‐ Loses, lessons and emerging issues - Nii‐Trebi, N.I.; Mughogho, T.S.; Abdulai, A.; Tetteh, F.; et al. (Reviews in Medical Virology, 2023)
Infectious diseases continue to be the leading cause of morbidity and mortality, and a formidable obstacle to the development and well‐being of people worldwide. Viruses account for more than half of infectious disease outbreaks that have plagued the world. The past century (1918/19–2019/20) has witnessed some of the worst viral disease outbreaks the world has recorded, with overwhelming impact especially in low‐ and middle‐income countries (LMIC). The frequency of viral dis ease outbreak appears to be increasing. Generally, although infectious diseases have afflicted the world for centuries and humankind has had opportunities to examine the nature of their emergence and mode of spread, almost every new outbreak poses a formidable challenge to humankind, beating the existing pandemic preparedness systems, if any, and causing significant losses. These underscore in adequacy in our understanding of the dynamics and preparedness against viral disease outbreaks that lead to epidemics and pandemics. Despite these challenges, the past 100 years of increasing frequencies of viral disease outbreaks have engendered significant improvements in response to epidemics and pandemics, and offered lessons to inform preparedness. Hence, the increasing frequency of emer gence of viral outbreaks and the challenges these outbreaks pose to humankind, call for the continued search for effective ways to tackle viral disease outbreaks in real time. Through a PRISMA‐based approach, this systematic review examines the outbreak of viral diseases in retrospect to decipher the outbreak patterns, losses inflicted on humanity and highlights lessons these offer for meaningful preparation against future viral disease outbreaks and pandemics
Research Article
Keywords: epidemics; infectious diseases; lessons; pandemics; viral outbreaks